The Pan-African School for Emerging Astronomers - (:unkn) unknown (My University, 2021)
The Pan-African School for Emerging Astronomers (PASEA) is an innovative short course for African university students, held by an African-led international collaboration. PASEA aims to build a critical mass of astronomers in Africa and exchange ideas about teaching across continents.
Keywords: African Research